STUDI ETNOBOTANI TUMBUHAN OBAT DI KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU - Safitri, Suci; Yolanda, Rofiza; Brahmana, Eti Meirina (Jurnal Ilmiah Mahasiswa FKIP Prodi Biologi, 2015)
Purpose of this study as to determine the species of plants used as traditional medicine, parts used and the efficacy of the plants by district community Rambah Samo. This study was conducted from November 2014 until January 2015. This study is qualitative with interview and survey technique. The result found 21 family from 38 species of plants are used as traditional medicine. Parts used in the form of leaves, rhizomes, roots, whole plant, stem, fruit and sap. How to use is by boiling, drops and engulfed. The most commonly treated diseases are blood sugar disease and cough.